2018
DOI: 10.1093/mnras/sty2759
|View full text |Cite
|
Sign up to set email alerts
|

Reignition of star formation in dwarf galaxies

Abstract: The Local Group hosts a number of dwarf galaxies that show evidence of periods of little to no star formation. We use a suite of cosmological simulations to study how star formation is reignited in such galaxies. We focus on isolated galaxies at z = 0 with halo masses between 9.2×10 8 M and 8.4×10 9 M , where star formation is typically shut off by reionization or by supernova feedback. Nearly 20% of these simulated galaxies later restart star formation, due to interactions with streams of gas in the intergala… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 87 publications
(127 reference statements)
8
58
0
Order By: Relevance
“…The metal-rich stars continue forming until the gas is depleted in this galaxy. Such interactions have been previously noted by Benítez-Llambay et al (2013) and Wright et al (2019). We show this passage through the cosmic filaments in greater detail in Fig.…”
Section: Ram Pressure-induced Star Formationsupporting
confidence: 80%
See 2 more Smart Citations
“…The metal-rich stars continue forming until the gas is depleted in this galaxy. Such interactions have been previously noted by Benítez-Llambay et al (2013) and Wright et al (2019). We show this passage through the cosmic filaments in greater detail in Fig.…”
Section: Ram Pressure-induced Star Formationsupporting
confidence: 80%
“…Another plausible formation path has been suggested by Wright et al (2019). These authors identified ram pressure as a mechanism for the reignition of star formation in field dwarf galaxies of stellar mass in the range 9.2×10 8 -8.4×10 9 M , and in which the star formation history has a prolonged gap.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…residual star formation can be fuelled by the galaxy's existing gas reservoir so as to produce SFHs similar to those observed for UFDs (Oñorbe et al 2015;Wheeler et al 2015). Additionally, reignition of star formation after initial suppression via reionization may produce short and late periods of star formation (Ledinauskas & Zubovas 2018;Wright et al 2019), such as that observed in Carina by Weisz et al (2014b). Observations in the Local Volume also broadly suggest that the mass scale at which quenching via reionization dominates is approximately M ∼ 10 5 M (e.g.…”
Section: Quenching On the Smallest Scalesmentioning
confidence: 74%
“…Indeed, modern hydrodynamic simulations of dwarf galaxies (e.g., Brooks & Zolotov 2014;Shen et al 2014;Oñorbe et al 2015;Wheeler et al 2015;Fitts et al 2017) have achieved great success in reproducing the observed properties, such as stellar mass content (e.g., Behroozi et al 2013;Moster et al 2013;Brook et al 2014;Garrison-Kimmel et al 2014;Read et al 2017;Jethwa et al 2018), cold gas content, star formation history (e.g., Tolstoy et al 2009;Weisz et al 2011Weisz et al , 2014Brown et al 2014), mass-metallicity relationship (e.g., McConnachie 2012; Kirby et al 2013Kirby et al , 2014, and stellar, gas kinematics, and morphological properties (e.g., McConnachie 2012) in field and satellite dwarf galaxies in the local Universe. With ever increasing resolution, simulations are now capable of probing the formation of ultra-faint dwarf galaxies (UFDs) and can be used to make predictions for upcoming deep surveys from telescopes such as the Vera C. Rubin Observatory (e.g., Fitts et al 2017;Revaz & Jablonka 2018;Wheeler et al 2019;Wright et al 2019a;Munshi et al 2019;Agertz et al 2020;Applebaum et al, in prep.). All these simulations have confirmed that, at least in the regime of classical dwarfs (M vir ∼ 10 10 M ), galactic outflows driven by stellar feedback are of critical importance to suppress star formation, reduce the stellar bulge-to-disc ratio, lower the intestellar medium (ISM) metallicity, and enrich the CGM.…”
Section: Introductionmentioning
confidence: 99%